Problems of standard controlling a scientific student work: legal grounds and practice - I. G. Pirozhkova (Библиосфера, 2019)
The article is devoted to the analysis of the legal basis of standardizing a student’s scientific research presentation in the form of a final qualifying work. There are differences in the federal regulatory framework and standardization current practice in this area; insufficiency of norm-definitions in the designated sphere; contradictions between the federal level of regulation and local acts of organizations that do not contain the necessary regulatory content. The author analyzes forms of the organization standards legitimization in the field of a qualifying work registration. The article clarifies gaps in the standardization control of students’ research by the analysis of the federal standard positions in the bibliography field and an organization standard (higher education institution). The author formulates recommendations on the content of the organization’s standards dictated by the dispositive nature of the state standard norms.